Clusters as institutional entrepreneurs: Lessons from Russia - Evgeniya Lupova-Henry; Samir Blili; Cinzia Dal Zotto (Journal of Innovation and Entrepreneurship, 2021)
In this article, we explore whether organized clusters can act as institutional entrepreneurs to create conditions favorable to innovation in their constituent members. We view self-aware and organized clusters as "context-embedded meta-organizations" which engage in deliberate decision- and strategy-making. As such, clusters are not only shaped by their environments, as "traditional" cluster approaches suggest but can also act upon these. Their ability to act as "change agents" is crucial in countries with high institutional barriers to innovation, such as most transition economies. Focusing on Russia, we conduct two cluster case studies to analyze the strategies these adopt to alter and shape their institutional environments. We find that clusters have a dual role as institutional entrepreneurs. First, these can act collectively to shape their environments due to the power they wield. Second, they can be mechanisms empowering their constituent actors, fostering their reflexivity and creativity, and allowing them to engage in institutional entrepreneurship. Moreover, both collective and individual cluster actors adopt "bricolage" approaches to institutional entrepreneurship to compensate for the lack of resources or institutional frameworks or avoid the pressures of ineffective institutions.
Keywords: 650; Cluster; Institutional contradictions; Institutional entrepreneurship; Meta-organization; Transition economy